Dimensions of water - Bartalini, Vladimir (Farol, 2025)
This article addresses aspects related to the poetic and mythical values of water, based on Gaston Bachelard’s studies condensed in Water and Dreams: an essay on the imagination of matter. Although Bachelard focused on examples taken from literature and poetry, an effort is made here to find their equivalents in landscape production, always seeking to highlight the relationships between water as a material and the forms it acquires. In the end, the focus is directed to the waters hidden by urbanization and the traces of their presence, betting on the possibilities that a poetic vision opens for landscape interventions in contemporary times.